2018
DOI: 10.1016/j.surg.2018.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human intestinal organoids into the mouse mesentery: A more physiologic and anatomic engraftment site

Abstract: The mouse mesentery is a viable location for the transplantation of human intestinal organoids, yielding grafts of reproducible size and quality. This improved model serves to advance functional and translational studies of human intestinal organoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 12 publications
0
42
0
2
Order By: Relevance
“…Similarly, microinjection of E. coli into the HIO lumen has permitted the study of epithelial response to early gut colonization (Hill et al, 2017a, 2017b). However, vascularization of HIOs has been restricted to in vivo models, whereby HIOs are transplanted into highly vascularized regions of immunocompromised mice (Cortez et al, 2018; Watson et al, 2014). In these environments, HIOs undergo extensive vascularization by the murine host tissue, and increase in complexity to resemble mature intestinal tissue (Finkbeiner et al, 2015b; Watson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, microinjection of E. coli into the HIO lumen has permitted the study of epithelial response to early gut colonization (Hill et al, 2017a, 2017b). However, vascularization of HIOs has been restricted to in vivo models, whereby HIOs are transplanted into highly vascularized regions of immunocompromised mice (Cortez et al, 2018; Watson et al, 2014). In these environments, HIOs undergo extensive vascularization by the murine host tissue, and increase in complexity to resemble mature intestinal tissue (Finkbeiner et al, 2015b; Watson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the mesentery shares a blood supply with the intestine, and is thought to contribute to intestinal function, including peristalsis, immune function, and tissue repair [7]. While our previous studies have demonstrated that the mesentery is a viable alternative site for HIO transplantation, a direct comparison between the two transplantation sites has not been performed [8]. Here, we aim to characterize potential similarities and differences between tHIOs engrafted into both sites.…”
Section: Introductionmentioning
confidence: 99%
“…For obvious reasons, they are also limited in their capacity to reach endpoint differentiation or full scale by virtue of their in vitro unperfused state. In large part, these models are also lacking a neural and immune system, although some approaches are including such cellular components either as additional elements during differentiation (Schlieve et al 2017) and/or transplantation for subsequent vascularization (Cortez et al 2018;Daviaud et al 2018).…”
Section: Building a Kidney Organoid From Pluripotent Stem Cellsmentioning
confidence: 99%